2000
DOI: 10.1088/0953-2048/14/1/304
|View full text |Cite
|
Sign up to set email alerts
|

Critical currents in Josephson junctions with macroscopic defects

Abstract: The critical currents in Josephson junctions of conventional superconductors with macroscopic defects are calculated for different defect critical current densities as a function of the magnetic field. We also study the evolution of the different modes with the defect position, at zero external field. We study the stability of the solutions and derive simple arguments, that could help the defect characterization. In most cases a reentrant behavior is seen, where both a maximum and a minimum current exist.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…However, the superconducting thin films consist of impurities or a great umber of grains contacting each other randomly and forming a network of Josephson junctions. 8 In fact, there is a report that the resistively shunted junction (RSJ) characteristics were obtained in granular YBCO thin film with bridge width of 0.1 mm. 9,10 Therefore, the certain critical bridge size, changing from RSJ characteristics to flux-flow type junction, exists and it depends on thin film quality such as crystallinity, uniformity or grain size.…”
Section: Resultsmentioning
confidence: 99%
“…However, the superconducting thin films consist of impurities or a great umber of grains contacting each other randomly and forming a network of Josephson junctions. 8 In fact, there is a report that the resistively shunted junction (RSJ) characteristics were obtained in granular YBCO thin film with bridge width of 0.1 mm. 9,10 Therefore, the certain critical bridge size, changing from RSJ characteristics to flux-flow type junction, exists and it depends on thin film quality such as crystallinity, uniformity or grain size.…”
Section: Resultsmentioning
confidence: 99%
“…Similar features are encountered in the problem of flux pinning from a macroscopic defect in a conventional s-wave junction. [17] We now examine the magnetic-interference pattern for the two symmetries where the bias current enters in the overlap geometry. In the d x 2 −y 2 + id xy -wave case, where θ = 0, this pattern has a symmetric form as we can see from Fig.…”
Section: Magnetic Fieldmentioning
confidence: 99%
“…-The static configurations of finite-length junction in the presence of an external magnetic field were studied by many authors. [1,8,9,14,[18][19][20][21]. Particularly, S.Pagano et al [18] for arbitrary junction lengths demonstrated the bifurcation curves of the fluxon states in the three different regimes typically observed: small, intermediate, and long junction.…”
mentioning
confidence: 96%